Regularities of chemical transformations in hydrotreating of vacuum gas oil derived from Kazakhstan oil - Belinskaya N. S. Natalia Sergeevna; Ivashkina E. N. Elena Nikolaevna; Oreshina A. A. Aleksandra Aleksandrovna; Vymyatnin E. K. Evgeny Konstantinovich; Arkenova S. B. Sania Bolatovna; Afanasjeva D. A. Darjya Aleksandrovna; Krivtsova N. I. Nadezhda Igorevna; Kaliev T. A. Toleubek Arystanbekovich (2021, 2021)
Title screen